Silicon toxicity induced by different concentrations and sources added to in vitro culture of epiphytic orchids - Mantovani, Cibele [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP]; de Mello Prado, Renato [UNESP]; de Souza, Jonas Pereira [UNESP]; Nascimento, Carolina Seno [UNESP]; Nascimento, Camila Seno [UNESP]; Gratão, Priscila Lupino [UNESP] (Elsevier, 2020)
Silicon has been added to the in vitro culture medium of orchids as a beneficial element that can successfully improve tissue culture. However, although supplemental Si may induce toxicity to the orchid culture depending on the source, there are no reports on the toxic concentrations of this element. To this end, this study conducted two experiments with two species of orchids, whose seedlings were obtained by sowing capsules containing mature seeds under aseptic conditions. At 120 days after sowing (DAS), seedlings of the Cymbidium atropurpureo and Dendrobium secundum orchids were recultivated in MS medium plus treatments in a 3 × 5 factorial scheme, with three silicon sources (nanosilica, potassium silicate and sodium silicate mixture, and monosilicic acid) at five different concentrations: 0.00 (control), 14.15, 28.30, 42.45, and 56.6 mmol L−1 Si following a completely randomized design with four repetitions and 10 seedlings each. The orchid culture ended after 300 DAS and the seedlings were removed from the flasks to evaluate the Si accumulation in plant tissues, the physiological data, pigments, biometric data and the survival percentage after acclimatization of 20 seedlings from each treatment. The results show that Si added to in vitro orchid cultivation may either favor growth or cause toxicity depending on the element source and concentration in the culture medium and the orchid species. Nanosilica at the 21.4 mmol L−1 Si concentration was the most promising source for orchid cultivation for Cymbidium atropurpureo. Further, monosilicic acid was considered the most toxic source due to the physiological damage caused to both Cymbidium atropurpureo and Dendrobium secundum at concentrations higher than 14.1 and 11.2 mmol L−1 Si, respectively.
Keywords: Cymbidium atropurpureo and Dendrobium secundum; Monosilicic acid; Nanosilica; Orchidaceae; Silicate